Hadith #2242 - Sunan Abi Dawud - al-Dhak bin Fyrwz al-Dylmy الضحاك بن فيروز الديلمي; Jarir bin Hazim bin Zayd جرير بن حازم بن زيد; Wahb bin Jarir bin Hazim bin Zayd وهب بن جرير بن حازم بن زيد; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yahya bin Ma'in يحيى بن معين; Yazid bin Abi Habib يزيد بن أبي حبيب (Sunan Abi Dawud)
The tradition mentioned above has also been transmitted by Qais bin Al Harith through a different chain of narrators to the same effect.
Grade: Sahih

Hadith #2444 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; ibn Abbas; Isma'il bin Umayya bin 'Amr إسماعيل بن أمية بن عمرو; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
When the Prophet (ﷺ) came to Medina, he found the Jews observing fast on the day of ‘Ashurah; so they were asked about it (by the Prophet). They said: This is a day on which Allah gave Moses domination over Pharaoh. We fast on it out of reverence to him. The Messenger of Allah (ﷺ) said: We have a closer connection with Moses than you have. He then gave orders that it should be observed.
Grade: Sahih

Hadith #2453 - Sunan Abi Dawud - Abdullah bin Abi Bakr bin Muh. b. 'Amr عبد الله بن أبي بكر بن محمد بن عمرو; Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin Salah al-Masri أحمد بن صالح المصري; al-Zuhri ابن شهاب الزهري‎, محمد بن مسلم; ibn Umar; Salim bin 'Abdullah bin 'Umar سالم بن عبد الله بن عمر بن الخطاب; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
I asked ‘Aishah: Would the Messenger of Allah (ﷺ) fast three days every month ? She replied: Yes. I asked: Which days in the month he used to fast ? She replied: He did not care which days of the month he fasted.
Grade: Sahih

Hadith #2497 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Ahmed bin 'Amr bin al-Sarh أحمد بن عمرو بن السرح أبو الطاهر; Sa'id bin Abi Ayoub سعيد بن أبي أيوب الخزاعي; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Zban bin Fa'id زبان بن فائد (Sunan Abi Dawud)
‘Abd Allah bin Amr reported the Apostle of Allaah(ﷺ) as saying “No warlike party will go out to fight in Allaah’s path and gain booty without getting beforehand two-thirds of their rewards in the next world and one-third (of their reward) will remain. And if they do not gain booty, they will get their rewards in full.
Grade: Sahih

Hadith #2641 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Anas ibn Malik; Hameed bin Abi Hameed حميد بن أبي حميد الطويل; Sulaiman bin Da'ud bin Da'ud سليمان بن داود بن داود بن علي; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Prophet (ﷺ) said: I am commanded to fight with men till they testify that there is no god but Allah, and that Muhammad is His servant and His Apostle, face our qiblah (direction of prayer), eat what we slaughter, and pray like us. When they do that, their life and property are unlawful for us except what is due to them. They will have the same rights as the Muslims have, and have the same responsibilities as the Muslims have.
Grade: Sahih

Hadith #3113 - Sunan Abi Dawud - Abu Sa'id al-Khudri; Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; al-Hasan bin 'Ali al-Halwani الحسن بن علي الخلال الحلواني; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
I heard the Messenger of Allah (ﷺ) say three days before his death: No one of you dies but he had good faith in Allah.
Grade: Sahih

Hadith #3323 - Sunan Abi Dawud - Ka'b bin 'Alqama bin Ka'b كعب بن علقمة بن كعب; Marthad bin 'Abdullah al-Yazni مرثد بن عبد الله اليزني; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Sa'id bin Abi Maryam سعيد بن أبي مريم; Uqba bin 'Amir al-Juhayni; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: The atonement for a vow is the same as for an oath. Abu Dawud said: This tradition has also been transmitted by ‘Amr b. al-Harith from Ka’b b. ‘Alqamah, from Ibn Shamasah on the authority of ‘Uqbah.
Grade: Sahih

Hadith #3457 - Sunan Abi Dawud - Abu Hurairah; Muhammad bin Hatm bin Yonus محمد بن حاتم بن يونس; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
We fought one of our battle, and encamped at a certain place. One of our companions sold a horse for a slave. After that they remained there for the rest of day and night. When the next morning came, they prepared themselves for departure. The buyer of the horse began to saddle it, but the seller was ashamed (of the transaction). He went to the man (buyer) and asked him to annul the transaction. The man refused to hand it over (the horse) to him. He said: AbuBarzah, the companion of the Prophet
Grade: Sahih

Hadith #3601 - Sunan Abi Dawud - Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Abu Hurairah; Ahmed bin Sa'id bin Sakhar أحمد بن سعيد بن صخر; Ata ibn Yasar عطاء بن يسار أبو محمد مولى ميمونة; Muhammad bin 'Amr bin 'Alqama محمد بن عمرو بن علقمة; Nafi' bin Yazid al-Kula'i نافع بن يزيد الكلاعي; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: The testimony of a deceitful man or woman, of an adulterer and adulteress, and of one who harbours rancour against his brother is not allowable.
Grade: Hasan

Hadith #3912 - Sunan Abi Dawud - Abu Hurairah; al-Q'qa' bin Hkym al-Knany القعقاع بن حكيم الكناني المدني; Dhakwan Abu Salah al-Saman al-Ziyat ذكوان أبو صالح السمان الزيات; Muhammad bin 'Abdul Rahim bin Abi Zuhayr محمد بن عبد الرحيم بن أبي زهير البزاز; Muhammad bin Ajlan al-Madni محمد بن عجلان المدني; Sa'id bin Abi Maryam سعيد بن أبي مريم; Ubaidullah bin Mqsm عبيد الله بن مقسم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي; Zayd bin Aslam زيد بن أسلم (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: There is no infection, no hamah, no other promising rain, and no serpent in a hungry belly.
Grade: Sahih

Hadith #4476 - Sunan Abi Dawud - Abdullah bin lahya'a bin 'Uqba عبد الله بن لهيعة بن عقبة الحضرمي; Abdullah bin Wahb عبد الله بن وهب بن مسلم القرشي; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Muhammad bin Abi Najiyya محمد بن أبي ناجية; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Prophet (ﷺ) did not prescribe any punishment for drinking wine. Ibn Abbas said: A man who had drunk wine and become intoxicated was found staggering on the road, so he was taken to the Prophet (ﷺ). When he was opposite al-Abbas’s house, he escaped, and going in to al-Abbas, he grasped hold of him. When that was mentioned to the Prophet (ﷺ), he laughed and said: Did he do that? and he gave no command regarding him. Abu Dawud said: This tradition of al-Hasan b. ‘Ali has been transmit
Grade: Sahih

Hadith #4881 - Sunan Abi Dawud - Abdullah bin Mubarak عبد الله بن المبارك; Isma'il bin Yahya al-Ma'afry إسماعيل بن يحيى المعافري المصري; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Prophet (ﷺ) said: If anyone eats once at the cost of a Muslim’s honour, Allah will give him a like amount of Jahannam to eat; if anyone clothes himself with a garment at the cost of a Muslim’s honour, Allah will clothe him with like amount of Jahannam; and if anyone puts himself in a position of reputation and show Allah will disgrace him with a place of reputation and show on the Day of Resurrection.
Grade: Sahih

Hadith #4930 - Sunan Abi Dawud - Abu Salama bin 'Abdur Rahman أبو سلمة بن عبد الرحمن بن عوف; Aisha bint Abi Bakr; Amarah bin Ghazya bin al-Harith عمارة بن غزية بن الحارث; Muhammad bin Awf bin Sufyan محمد بن عوف بن سفيان الطائي; Muhammad bin Ibrahim bin al-Harith محمد بن إبراهيم بن الحارث; Sa'id bin Abi Maryam سعيد بن أبي مريم; Yahya bin Ayoub al-Ghafiqi يحيى بن أيوب الغافقي (Sunan Abi Dawud)
The Prophet (May peace be upon him) cursed effeminate men (mukhannathan) and women who imitated men, saying: Put them out of your houses, and put so-and-so out. (that is to say, the effeminate men)
Grade: Sahih